LG in India (C) : sustaining competitive advantage - Salwan, Prashant (SAGE Knowledge. Cases., 2011)
LG was market leader in nearly all its product lines and segments in consumer electronics in India in 2007. LGIL had appointed a new MD who had to develop strategies to enable the company to sustain its market position. This case details the distribution, product development and service focus of LG, together with changing consumer behavior up to the present time with projections for strategy into the future.